One-Price Marketing Trend: Balancing Business Strategy and Legal Challenges in the Practice of Toko Serba 35.000 - Andani, Widia Ayu; Susilawati, Cucu (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2023)
Abstract: Toko Serba 35.000, renowned for its one-pricing at Rp. 35,000, has emerged as a compelling alternative for consumers seeking affordability. However, its widespread popularity has introduced ambiguity regarding the true market value of its products. This study delves into the implementation and legal implications of the one-price marketing strategy at Toko Serba 35.000, focusing on Islamic economic law and positive law. Employing a qualitative descriptive approach, the research involved observations and interviews conducted at Toko Serba 35.000 in Rengasdengklok Subdistrict, Karawang. Findings indicate that the pricing strategy is rooted in capital, profit, and market competition considerations, with a standardized price of Rp. 35,000. Sharia economic law analysis reveals a potential violation of pricing integrity or 'tadlis' and speculative uncertainty or 'gharar' due to the actual prices differing from promotional claims. Meanwhile, statutory regulations such as Law Number 8 of 1999 on Consumer Protection and Trade Minister Regulation Number 35/M-DAG/PER/7/2013 mandate clear pricing, a requirement not met by this strategy. Despite this, the micro-enterprise status of Toko Serba 35.000 exempts it from certain regulations. Consequently, while compliant with formal regulations, Toko Serba 35.000 introduces inconsistencies with principles of Sharia economic law.Abstrak: Toko Serba 35.000, dengan harga seragam Rp. 35.000, telah menjadi alterbatif yang menarik bagi konsumen dalam memenuhi kebutuhan. Namun, popularitasnya menciptakan ketidakjelasan nilai pasar suatu produk. Penelitian ini mengeksplorasi penerapan dan implikasi hukum strategi pemasaran satu harga di Toko Serba 35.000, dengan fokus pada hukum ekonomi syariah dan hukum positif. Menggunakan pendekatan deskriptif kualitatif, penelitian dilakukan melalui observasi dan wawancara di Toko Serba 35.000, Kecamatan Rengasdengklok, Karawang. Hasilnya mengindikasikan bahwa strategi ini didasarkan pada modal, keuntungan, dan persaingan, dengan harga terendah Rp. 35.000. Analisis hukum ekonomi syariah menunjukkan pelanggaran penetapan harga atau tadlis, dan memiliki potensi gharar karena harga sebenarnya tidak sesuai dengan promosi. Sementara Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen dan Peraturan Menteri Perdagangan Nomor 35/M-DAG/PER/7/2013 mengamanatkan pencantuman harga yang jelas, yang tidak terpenuhi oleh strategi ini. Meski demikian, toko ini tidak melanggar regulasi karena statusnya sebagai usaha mikro. Implikasinya, meskipun sesuai dengan peraturan formal, Toko Serba 35.000 menimbulkan ketidaksesuaian dengan prinsip hukum ekonomi syariah